HLA-B27-associated uveitis: From pathogenesis to therapy - A. B. Demina; T. V. Dubinina; Sh. F. Erdes (Современная ревматология, 2016)
Uveitis is the inflammation of the uvea, which generally occurs in young people and may be accompanied by serious complications leading to disability. The review analyzes the data of Russian and foreign investigations on the pathogenesis of HLA-B27-associated uveitis occurring in different diseases from a group of seronegative spondyloarthritides (SpA) and also discusses current therapeutic approaches in this disease.Since the late 20th century, there has been rapid progress in studying the pathogenesis of HLA-B27-associated uveitis and in identifying the genetic factors predisposing to this pathology. Investigations of HLA-B27 antigen and its alleles are being continued. Tumor necrosis factor-α (TNF-α), the higher levels of which in blood, synovial fluid, and ocular fluid in rheumatic diseases has been proven in many works of both foreign and Russian scientists, is most studied among the inflammatory mediators. Due to the key role of this cytokine in the development of inflammation, drugs inhibiting TNF-α activity have been designed and successfully used in the past decade, which results in partial and occasionally stable remission.